2015
DOI: 10.2500/ajra.2015.29.4115
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Survival in Patients with Acute Invasive Fungal Rhinosinusitis

Abstract: Overall survival rate remained approximately 50% in patients with AIFR. The prognosis of AIFR is significantly influenced by underlying diseases, accompanying neutropenia, CRP levels, symptom duration, involvement of septum, and the presence of facial swelling. Elevation of CRP, in particular, was an independent predictor of poor outcomes and should be monitored appropriately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
79
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(92 citation statements)
references
References 22 publications
10
79
3
Order By: Relevance
“…Multi-involvement and complications are commonly encountered in both groups. Cranial neuropathy, visual loss, and orbital pain were the most common complications encountered in cases of fungal rhinosinusitis, according to Cho et al [9]. Similarly, headache, dizziness, and visual loss were the most common complications in our patients, and orbital involvement is a feature of both types of fungal rhinosinusitis.…”
Section: Discussionsupporting
confidence: 74%
“…Multi-involvement and complications are commonly encountered in both groups. Cranial neuropathy, visual loss, and orbital pain were the most common complications encountered in cases of fungal rhinosinusitis, according to Cho et al [9]. Similarly, headache, dizziness, and visual loss were the most common complications in our patients, and orbital involvement is a feature of both types of fungal rhinosinusitis.…”
Section: Discussionsupporting
confidence: 74%
“…In a study conducted by Cho et al, 11 CRP levels and neutropenia were associated with the prognosis of AIFR. Among the laboratory parameters, lower neutrophil and lymphocyte counts were associated with a worse prognosis (p Ͻ 0.05).…”
Section: Discussionmentioning
confidence: 98%
“…1,5,9,11,18,19 The median follow-up time was 58 days (IQR ϭ 304 days) in our study. The overall mortality rate was 64.9%.…”
Section: Discussionmentioning
confidence: 98%
“…Chakrabarti et al , 4 in north India, found that the most common species that caused fungal rhinosinusitis was Aspergillus ; however, Mucor was the most common species isolated in our study. According to Cho et al , 8 cranial neuropathy, visual loss, and orbital pain were the most common complications encountered in cases of fungal rhinosinusitis. Similarly, in our study, orbital cellulitis and cranial nerve palsies were the most common complications (Table 1).…”
Section: Discussionmentioning
confidence: 99%